Marking sutures to orientate specimens of basal cell carcinoma: do they really make a difference?. Issue 6 (July 2016) - Tullett, M.; Whittaker, M.; Walsh, S.
Abstract: Traditionally, marking sutures have been used to orientate specimens of non-melanomatous skin cancers, and they provide an identifiable point as a reference for monitoring and further treatment. For histopathological purposes, the orientated specimen is marked with different inks, which enables measurement to the nearest lateral and deep margins, and if invaded, guides further excision. We retrospectively analysed 688 specimens of basal cell carcinoma (BCC) from the head and neck from two separate years: 2010 and 2012. Marking sutures were used in 663 (96%) cases. There were 21 invaded margins (3%), 17 (81%) at the lateral margin and 4 (19%) at the deep margin. Of the 17 with invaded lateral margins, 10 were from the nose, and the remaining 7 from other sites including the ear (n = 2), and neck, forehead, temple, eyelid, and cheek (n = 1 each). Of the 663 marked specimens, the marking stitch was useful in only one patient who needed another operation (0.2%). We suggest that routine orientation of BCC, even from high risk areas, is not necessary. If the operating surgeon questions the size of the margin when a lesion is ill-defined or of a high-risk histological subtype, then excision with monitored en-face margins should be considered with traditional Mohs surgery or a reliable modified version.